Perancangan Sistem Penjadwalan Perkuliahan Berbasis Website Menggunakan Algortima Genetika - Arif Prio Pambudi; Ari Waluyo; El Vionna Laellyn Nurul Fatich (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The development of information technology has overgrown and has had a positive impact on human activities. One of the information technology developments is artificial intelligence (Artificial Intelligence) that can help solve a complex problem, sometimes even faster and more reliably than solving problems by themselves. Various types of artificial intelligence have been developed at this time, one of which is genetic algorithms. Genetic algorithms can help solve lecture scheduling problems hoping that the lecture scheduling process can be carried out quickly, accurately, effectively, and efficiently. At Politeknik Dharma Patria Kebumen, the lecture scheduling process is computerized with the Microsoft Excel application. The system is considered less effective because it requires a high accuracy so that there are no clashes in the lecture schedule, and the process is long and takes a long time. A website-based lecture scheduling information system is needed based on these problems by utilizing genetic algorithms as an automation method. In comparison, waterfall is the method that used in this information system development, with the system modeling using the Undefined Modeling Language (UML). Based on the scheduling system trial results, the most effective time for the lecture scheduling process was 00:12:17 with a population value of 10, a Pm value of 0.4, and a Pc value of 0.7. After designing a website-based lecture scheduling information system using the genetic algorithm, the lecture scheduling process can be carried out quickly, accurately, effectively, and efficiently at the beginning of each semester.